Evolution of genome size and genomic GC content in carnivorous holokinetics (Droseraceae) - Veleba, Adam (Ann Bot, 2017)
Background and Aims Studies in the carnivorous family Lentibulariaceae in the last years resulted in the discovery of the smallest plant genomes and an unusual pattern of genomic GC content evolution. However, scarcity of genomic data in other carnivorous clades still prevents a generalization of the observed patterns. Here the aim was to fill this gap by mapping genome evolution in the second largest carnivorous family, Droseraceae, where this evolution may be affected by chromosomal holokinetism in Drosera. Methods The genome size and genomic GC content of 71 Droseraceae species were measured by flow cytometry. A dated phylogeny was constructed, and the evolution of both genomic parameters and their relationship to species climatic niches were tested using phylogeny-based statistics. Key Results The 2C genome size of Droseraceae varied between 488 and 10 927 Mbp, and the GC content ranged between 37·1 and 44·7 %. The genome sizes and genomic GC content of carnivorous and holocentric species did not differ from those of their non-carnivorous and monocentric relatives. The genomic GC content positively correlated with genome size and annual temperature fluctuations. The genome size and chromosome numbers were inversely correlated in the Australian clade of Drosera. Conclusions Our results indicate that neither carnivory (nutrient scarcity) nor the holokinetism have a prominent effect on size and DNA base composition of Droseraceae genomes. However, the holokinetic drive seems to affect karyotype evolution in one of the major clades of Drosera. Our survey confirmed that the evolution of GC content is tightly connected with the evolution of genome size and also with environmental conditions.